2018
DOI: 10.3390/ijerph15122679
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Formal and Informal Care by Community-Living People with Dementia: A Comparative Study between Sweden and Italy

Abstract: Background: Dementia is a public health priority with a dramatic social and economic impact on people with dementia (PwD), their caregivers and societies. The aim of this study was to contribute to the knowledge on how utilization of formal and informal care varies between Sweden and Italy. Methods: Data were retrieved from two trials: TECH@HOME (Sweden) and UP-TECH (Italy). The sample consisted of 89 Swedish and 317 Italian dyads (PwD and caregivers). Using bivariate analysis, we compared demographic characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…The Swedish universal healthcare system has been criticised for its difficulties in addressing informal caregivers (Johansson, Long, & Parker, ). Also, one study of informal caregivers to dementia care receivers showed that informal caregivers in Sweden spend less time in their caregiving when compared with caregivers in another European country, Italy (Chiatti et al, ). Systems for supporting informal caregivers are present in other European countries as well, such as the United Kingdom's Carer's Assessments for adult carers of people who are disabled, ill or elderly and the Carer Support Needs Assessment Tool (Austin, Ewing, & Grande, ).…”
Section: Discussionmentioning
confidence: 99%
“…The Swedish universal healthcare system has been criticised for its difficulties in addressing informal caregivers (Johansson, Long, & Parker, ). Also, one study of informal caregivers to dementia care receivers showed that informal caregivers in Sweden spend less time in their caregiving when compared with caregivers in another European country, Italy (Chiatti et al, ). Systems for supporting informal caregivers are present in other European countries as well, such as the United Kingdom's Carer's Assessments for adult carers of people who are disabled, ill or elderly and the Carer Support Needs Assessment Tool (Austin, Ewing, & Grande, ).…”
Section: Discussionmentioning
confidence: 99%
“…Dependency has demonstrated rapid growth in recent years [1]. Although the availability of care and services for may differ significantly across countries [2], in the countries of the Organization for Economic Cooperation and Development more than one in 10 adults assumes the role of non-professional caregiver [3].…”
Section: Introductionmentioning
confidence: 99%
“…The continuous deterioration caused by the disease makes those who are affected require more care. Consequently, people with dementia require assistance to perform activities of daily living (ADLs) such as bathing, clothing, feeding and using the toilet [9,10]. Dementia caregivers' wellbeing can be promoted, improved and maintained by applying treatment modalities such as pharmacological, psychological and psychosocial interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers' burden is associated with health problems such as compassion fatigue that force some family caregivers to relinquish care roles of their loved ones to long-term care [13]. Dementia caregivers can be categorised into informal/family caregivers and formal/professional caregivers [7,9]. The informal caregivers' role is gendered.…”
Section: Introductionmentioning
confidence: 99%